Assessment of the LGSP project on Human Resource Development in the Municipality of New Lucena - Damasco, Lorelen A.
This study aims to determine the outputs or effects of the LGSP project entitled, "Human Resource development Program for Improvement of Service Delivery" in the Municipality of New Lucena. Primarily, its objective is to assess the efficiency/effectiveness of personnel on the delivery of services/program prior and after the LGSP project intervention in the said municipality. In the process of this study, it was found out that the project has come up with two systes which are now being installed and used in the said municipality. These are the performance Appraisal and Information and Communication Systems. The performance of the personnel however, showed considerable effects in the service they have delivered. and efforts made by LGSP as to the impact of the project is not that highly tangible up to this time.